Nodular Fasciitis: False Positive on 18F-Piflufolastat and 11C-Choline PET/CT. (12th April 2023) - Pitot, Marika A.; Broski, Stephen M.; Thompson, Scott M.; Woodrum, David A.; Powell, Garret M.
Abstract: PET/CT plays a crucial role in the management of prostate cancer with several emerging and established radiopharmaceuticals, including 18 F-piflufolastat and 11 C-choline. These radiotracers are thought to be relatively specific to prostate cancer; however, uptake has also been demonstrated in other benign and malignant lesions. Nodular fasciitis is a rapidly growing benign soft tissue neoplasm that is typically self-limiting. Although a few case reports describe 68 Ga-PSMA uptake in nodular fasciitis, uptake of 11 C-choline and other PSMA-targeted PET probes, including 18 F-piflufolastat, have not previously been reported. We present a novel case of nodular fasciitis demonstrating both 18 F-piflufolastat and 11 C-choline avidity.